228k views
5 votes
Solve the following IVP:

2. 2x^2 +y^2 +xyy′ =0, x>0, y(1)=1

1 Answer

2 votes

Answer:


x^2y^2+x^4=2

Explanation:

The given differential equation is:


2x^2+y^2+xyy'=0,x\:>\:0,y(1)=1

We rewrite this as


2x^2+y^2+xy(dy)/(dx)=0,x\:>\:0,y(1)=1

We make
(dy)/(dx) the subject to get:


(dy)/(dx)=(-2x^2-y^2)/(xy)....a homogeneous equation.


(dy)/(dx)=-2((x)/(y))-((y)/(x))

We use the following substitutions to obtain a seperable equation:


y=vx,(dy)/(dx)=v+x(dv)/(dx),v=(y)/(x),\:and\:(1)/(v)=(x)/(y).

This implies that:


v+(xdv)/(dx)=(-2)/(v)-v


(xdv)/(dx)=(-2)/(v)-2v


(xdv)/(dx)=(-2-2v^2)/(v)


(v)/(-2-2v^2)dv=(dx)/(x)

We integrate both sides to obtain:


\int (v)/(-2-2v^2)dv=\int (dx)/(x)


(-\ln|2v^2+2|)/(4)=\ln x+\ln K


-\ln|2v^2+2|=4(\ln x+\ln K)


\ln ((1)/(2v^2+2))=4\ln (Kx)


\ln ((1)/(2v^2+2))=\ln(K^4x^4)


(1)/(2v^2+2)=Cx^4


Cx^4(2v^2+2)=1

We substitute
v^2=(y^2)/(x^2) to get:


Cx^4(2*(y^2)/(x^2)+2)=1

We substitute x=1,y=1 from the initial conditions.


C(1)^4(2*(1^2)/(1^2)+2)=1


4C=1


C=(1)/(4)

Our solution now becomes:


x^2(2y^2+2x^2)=4


x^2(y^2+x^2)=2


x^2y^2+x^4=2

User Federico Zancan
by
4.6k points